Digital competency in rural schools of Jammu and Kashmir: A case study of Paddar Sub-division - Mohammad, Suleiman Ibrahim Shelash; Panda, S. K.; Singh, Ravail; Raja, N; Vasudevan, Asokan (International Journal of Innovative Research and Scientific Studies, 2025)
The current era is the era of digital technology. Its inclusion has affected all aspects of society, including education. Digital technology is acting as a means towards the enhancement of learning outcomes and the quality of education, but the integration of such technologies in schools for making changes and innovation is not enough; it requires digitally competent teachers to facilitate the use of digital technologies in education. Digital technology in schools has become an influential strategy for teachers to use in support of their pedagogical practices and student learning. Its integration into education has revolutionized teaching and learning and offered new opportunities to enhance educational experiences and outcomes. The objectives of the study are to identify the problems and challenges in the integration of digital technology in the schools of the Paddar sub-division and to suggest remedies to solve the problems and handle the challenges in the integration of digital technology. A qualitative interpretive research design was applied to identify the problems and challenges faced in the integration of digital technology in the schools of rural areas of Jammu and Kashmir Union Territory. The samples were collected from 28 government (9 secondary and 19 elementary) schools and five private elementary schools. Five students (28×5=140) and two teachers (28×2=56) were selected from each government school, and ten students (5×10=50) and four teachers (4×5=20) were selected from each private school studying in the 10th and 8th classes. The data were collected by employing separate interview schedules for students and teachers, along with participant observations, and checklists were employed to identify the digital facilities in the schools. The findings of the study revealed that the major problems were the lack of digital infrastructural facilities in the schools of rural areas, the inclusion of ICT as a separate subject in the curricula, and the lack of efficiency in using digital technologies among the students and teachers. The lack of digital infrastructural facilities in the schools of rural areas of Jammu and Kashmir Union Territory of India and the lack of digital competency among the students and teachers were the major problems.